A Preliminary Study of Perceptions of Community Hospitals in Cairo, Egypt: Towards Healthy Environmental Design - Iskander, Veronica (AUC Knowledge Fountain, 2023)
Hospitals are a place that people dread and often avoid. Negative experiences in hospitals can contribute to pain and suffering, as well as to stress, loss of control and overall discomfort. While architecture has the power to heal when designed and maintained, it also has the power to harm if not done right. Each architectural element then has the potential to either reduce stress or contribute to it. From the location of the hospital to the colors used, there are many factors that work together to create a safe welcoming space promoting healing for all. In this study, a checklist was deduced from the literature that specified the main architectural elements needed to be included in the design process in order to reduce stress within the overall hospital experience. This checklist was used as a baseline to study four private hospitals in Cairo, Egypt through observational visits to explore the design decisions currently made in the hospital sector that may not be aimed at patient healing or lowering stress levels. These results were then compared to 128 survey responses which were collected from both the patients and visitors of these four hospitals where their experience with the environment was gathered. This study discovered that while hospitals do in fact work on providing a positive environment for patients, the design decisions are neither evidence based nor focused on stress reducing elements. Therefore, stress- related experiences are not controlled by the architectural elements but rather primarily by the services provided in each hospital.